2005
DOI: 10.5713/ajas.2006.224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lycopene and Vitamin E on Egg Production, Antioxidant Status and Cholesterol Levels in Japanese Quail

Abstract: Japanese Quails were used to evaluate the effects of dietary supplementation with vitamin E (dl-a-tocopheryl-acetate), lycopene, and their combination on egg production, egg quality, concentrations of malondialdehyde (MDA), vitamin E, A and cholesterol in serum and egg yolk. Quails (n = 120; 55 d old) were divided into four groups (n = 30/group) and fed a basal diet or the basal diet supplemented with lycopene (100 mg/kg diet), vitamin E (250 mg dl-α-tocopheryl-acetate/kg diet) or a combination of lycopene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 58 publications
5
44
0
Order By: Relevance
“…However, Sahin et al (2008) and Akdemir et al (2012) noted that dietary LP or tomato-related products increased feed intake and egg production with the increasing LP supplementation in Japanese quails or laying hens. Sahin et al (2006b) observed that dietary LP at 100 ppm did not affect feed intake and egg weight, but increased egg production in Japanese quails. Egg qualities, i.e., eggshell strength, thickness, or Haugh unit were not affected by dietary treatments as reported previously (Kim et al, 2008;Rotolo et al, 2010;Akdemir et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Sahin et al (2008) and Akdemir et al (2012) noted that dietary LP or tomato-related products increased feed intake and egg production with the increasing LP supplementation in Japanese quails or laying hens. Sahin et al (2006b) observed that dietary LP at 100 ppm did not affect feed intake and egg weight, but increased egg production in Japanese quails. Egg qualities, i.e., eggshell strength, thickness, or Haugh unit were not affected by dietary treatments as reported previously (Kim et al, 2008;Rotolo et al, 2010;Akdemir et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to our finding, a lipid lowering effect by dietary LP was reported. For example, dietary LP at levels of 50 to 200 ppm decreased triglyceride and total cholesterol concentrations in serum samples (Sahin et al, 2006a) and total cholesterol concentrations both in serum and egg yolk (Sahin et al, 2006b) in quails. Sun et al (2014b) reported that dietary LP in the range 20 to 80 mg/kg diet lowered serum total cholesterol, but not triglyceride, in breeding hens.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms that may explain the association of dietary Se and α-tocopherol with yolk cholesterol concentration is not clear and relevant information in the literature is limited. Sahin et al (2006) reported that in Japanese quails fed supplemental lycopene and vitamin E, separately or in combination, decreased yolk cholesterol concentration and increased serum and egg yolk vitamin E and A.…”
Section: Selenium and α-Tocopherol Concentration In Eggsmentioning
confidence: 99%
“…E is not synthesized by poultry, and its availability is through exogenous administration only 10 . Vit E plays an important role in poultry industry because of its beneficial effect on the cell membrane integrity, immune system and reproduction performance 8,12,14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…E) has been reported an excellent biological functions as a natural antioxidant prevent the oxidation of unsaturated lipid materials within cells, thus protecting the cell membrane oxidative damage [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%